Forecasting in a changing world: from the great recession to the COVID-19 pandemic - Mariia Artemova; Francisco Blasques; Siem Jan Koopman; Zhaokun Zhang (Tinbergen Institute, 2021)
We develop a new targeted maximum likelihood estimation method that provides improved forecasting for misspecified linear autoregressive models. The method weighs data points in the observed sample and is useful in the presence of data generating processes featuring structural breaks, complex nonlinearities, or other time-varying properties which cannot be easily captured by model design. Additionally, the method reduces to classical maximum likelihood when the model is well specified, which results in weights which are set uniformly to one. We show how the optimal weights can be set by means of a cross-validation procedure. In a set of Monte Carlo experiments we reveal that the estimation method can significantly improve the forecasting accuracy of autoregressive models. In an empirical study concerned with forecasting the U.S. Industrial Production, we show that the forecast accuracy during the Great Recession can be significantly improved by giving greater weight to observations associated with past recessions. We further establish that the same empirical finding can be found for the 2008-2009 global financial crisis, for different macroeconomic time series, and for the COVID-19 recession in 2020.
Keywords: C10; C22; C32; C51; 330; Autoregressive Models; Cross-Validation; Kullback-Leibler Divergence; Stationarity and Ergodicity; Macroeconomic Time Series